In defence of the rationality of ethics. "Veritatis Splendor" and a robust conception of moral agency - Cebula, Adam (Studia Philosophiae Christianae, 2017)
The central metaethical contention of "Veritatis Splendor" is that an indispensable element of any plausible conception of moral agency must always be a specific notion of a moral act – an act executed by a moral agent. In my paper I focus on the way in which the interpretation of a moral act as a specific enterprise fully identifiable and determined by its clearly outlined aim (the object of an act) informs the concept of moral agency – human faculty of deliberating upon and performing moral acts. In view of the pledge made by the encyclical’s author not to “impose upon the faithful any particular theological system, still less a philosophical one” I try to demonstrate that the dependence (or perhaps interdependence) in question is of the most basic nature and can thus be construed as a key condition for a genuinely rational character of any ethical theory.